Evaluating Human Resource Accounting In Relation To Employee Compensation And Performance In Private Hospitals Of Manipur - Maibam Angkita Devi, Prof. Ningombam Jayanti (Journal of Informatics Education and Research, 2025)
This investigationevaluates complex links between Human Resource Accounting (HRA) processes, employee compensation, and performance in Manipur's private hospitals. A study of 300 respondents from Manipur's hospitals was conducted to collect information on performance appraisal methods, remuneration and benefits, and HRA procedures. The study's goals were to evaluate the efficacy of performance appraisal systems and their relationship to HRA practices, to examine impact of compensation, moreover, benefits on employee performance, and to analyse relationship between HRA practices and employee remuneration. The study’s conclusions offer insightful information on the strategic management of hospital human resources, pointing out areas that need work to boost worker enthusiasm, output, and organizational effectiveness. Hospital managers and legislators may use the study’s findings to guide the creation of efficient HRA procedures, pay plans, and performance evaluation systems that promote organizational success. With useful ramifications for hospital administration, this study adds to the corpus of evidence already available on HRA procedures, employee pay, and performance in the healthcare industry.